Experimental study of fretting fatigue in dovetail assembly considering temperature effect based on damage mechanics method. (January 2022) - Sun, Debin; Huo, Junzhou; Chen, Hao; Dong, Zhengliang; Ren, Rong
Highlights: A high-temperature fretting fatigue life prediction model considering the temperature effect is established. A criterion suitable for the high temperature fretting fatigue crack initiation failure is proposed. Fretting fatigue tests were designed and carried out at room temperature and high temperature. Abstract: Fretting fatigue of dovetail structure of aero-engine compressor is a very complex phenomenon, which is affected by different factors such as temperature, load, friction coefficient, and arc radius, etc. Aiming at the problem of the high-temperature fretting fatigue life prediction of dovetail structure, the high-temperature effect on fretting fatigue life is analyzed, and then the fretting fatigue life prediction model is established considering the temperature effect by introducing temperature equivalent factor based on the circular flat contact theory and continuous damage mechanics theory. Besides, the criterion of fretting fatigue cracks initiation failure is proposed based on the displacement–strain joint monitoring method in the fretting fatigue tests. The experiment results show that the proposed fretting fatigue life prediction model has a high life prediction ability within ± 2.0 times error band. It is found that the traditional damage mechanics accumulation model cannot reflect the change of fretting fatigue damage only by changing the material performance parameters in a high-temperature environment, needing temperature correction and the proposed fretting fatigue life prediction model considering temperature effect in the exponential form of temperature ratio is feasible.